ANALISIS KESULITAN MAHASISWA DALAM MENYELESAIKAN MASALAH DISTRIBUSI FREKUENSI PADA MATA KULIAH STATISTIKA DITINJAU DARI KEMAMPUAN KONEKSI MATEMATIS - Ferdinandus Ardian Ali; Viviana Murni (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This research is of a qualitative type, which aims to find out in depth about what causes it, why it is experienced, and how students experience difficulties in solving frequency distribution problems in statistics courses. This research was conducted at the Catholic University of Indonesia Santu Paulus Ruteng in the odd semester of the 2022/2023 academic year. The selection of research subjects used a purposive technique so that 1 KKMR subject, 1 KKMS subject and 1 KKMT subject were selected. The main instrument is the researcher himself while the supporting instruments use tests and interviews. Data collection uses triangulation techniques (test and interview techniques). Data analysis is done by reducing data, presenting data and drawing conclusions or verification. The results showed that KKMR subjects experienced more difficulties than KKMS subjects and KKMT subjects, KKMS subjects experienced more difficulties than KKMT subjects, while KKMT subjects experienced fewer difficulties than KKMR subjects and KKMS subjects. KKMR subject difficulties due to low memory of arithmetic operation rules, low memory of formulas, and low memory of connection rules in math material, and KKMS subject difficulties due to low memory of arithmetic operation rules, and low memory of connection rules in material mathematics, while the difficulty of the KKMT subject was caused by mistakes and low memory of connection rules in mathematics material.